STUDENTS MOTIVATION TOWARDS GLOBAL ASSESSMENT CERTIFICATE CURRICULUM: A SURVEY STUDY - Hasanah, Uswatun; Farani, Rizki (LLT Journal: A Journal on Language and Language Teaching, 2020)
This paper aims to identify motivation of students to learn English as Foreign Language for Global Assessment Certificate (GAC) curriculum in international private high school in Yogyakarta. There were 46 GAC students from grade X, XI and XII involved in this study. The level of motivation was measured by using Attitude/ Motivation Test Battery (AMTB), consists of 5 domains, desire to learn English, attitudes toward learning English, the interest in foreign language, language class anxiety and language use anxiety. The results show that the motivation of the students to learn English as EFL was at high and moderate level. The students are able to speak English well but they need improvement on self-confidence in English. The survey implies that students well perceived English as an important means for their carrier prospects and way to enhance their knowledge.